If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2x = -3 Combine like terms: 6x + -2x = 4x 4x = -3 Solving 4x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = -0.75 Simplifying x = -0.75
| 0=12p-48 | | 6x-4=2x+4 | | 3x+3y=75 | | 29=38+x | | 29=38+2 | | 8+4k=10+k | | 6x+12=0 | | 3x+3y+105=180 | | 78-y=7 | | 36=-4x+56 | | 5x+3x+3y=180 | | -2x-98=2 | | -70+5x=-20 | | 9x-9=180 | | 6*0-y=7 | | -12(6n+3)=9(-9n+9) | | 8x+y=20x+3y | | -38+17y+9=4(5y-3)-2 | | 20x+16y=180 | | 6x-(-19)=7 | | -3t-8+7t=34+9t-2 | | 9a=6(a+4) | | 3y-9y=4 | | 2t+7=-7 | | 8-8=17m-6m | | 6(8x+3)=48x | | 12x+11= | | 4x-x=-1 | | 6(5x+7)=30x | | 8m-5=13 | | (8x-10)=15+5(x-10) | | 5y=-3 |